IDENTIFYING THE CARBON FOOTPRINT OF FORMWORK MATERIAL DELIVERY IN BUILDING CONSTRUCTION PROJECTS - Tubagus Arsalan Raihan Alauddin; Ryan Faza Prasetyo (International Journal on Livable Space, 2023)
Sustainable construction is a way of implementing sustainable development of the construction industry and infrastructure through building a better quality of life, and minimizing the use of resources and energy in order to actualize The 2030 Agenda for Sustainable Development. The use of construction materials is one source of carbon dioxide emissions and material delivery is one of the stages in the construction material supply chain that has the potential to cause CO2 emissions, one of which is the use of formwork. Global warming is closely related to carbon footprint. The research was done by surveying the building construction project followed by data processing which aims to find out how much carbon emissions are generated by construction projects in the contracting process, delivery, formwork fabrication process, and the use of tower cranes and find out what factors contribute to the carbon footprint and what processes are most significant in producing carbon footprints. The results show that carbon emissions for 28 floors amounted to 84,815.1037 kg.CO2 and by doing 2 scenarios in which scenario 1 maximizes the carrying capacity of each delivery truck during the delivery process and delivery for all the needs of 1 tower is carried out during the GF floor and first floor work, the resulting carbon emission efficiency is 2289.0626 kg. CO2 and in scenario 2 where the delivery of multiplexes for the needs of only 1 floor, which makes delivery carried out for each floor and makes the delivery distance half the actual distance, the resulting carbon emission efficiency is 4628.7909 kg.CO2.